Exercise behaviour, enjoyment and boredom: A test of the 2 × 2 model of perfectionism. Issue 6 (1st November 2020) - Deck, Sarah; Roberts, Ross; Hall, Craig; Kouali, Despina
Abstract : Previous research investigating the role or perfectionism in exercise has been limited by both the method of investigation (largely examining independent effects of perfectionism dimensions), and the outcome variables that have been studied (mostly maladaptive outcomes). The purpose of the current study was to investigate the role of perfectionism on exercise behaviour, boredom, and enjoyment using the recently established 2 × 2 model of perfectionism. This model proposes that different forms of perfectionism, such as self-oriented (SOP) and socially prescribed perfectionism (SPP), will interact to influence different outcomes. One hundred and ninety-four college students completed a multi-section inventory comprised of demographics, the Multidimensional Perfectionism Scale (MPS; Hewitt, P. L., Flett, G. L., Turnbull-Donovan, W., & Mikail, S. F. [1991]. The Multidimensional perfectionism scale: Reliability, validity, and psychometric properties in psychiatric samples. Psychological Assessment: A Journal of Consulting and Clinical Psychology, 3(3), 464–468. doi:10.1037/1040.3.3.464), the Physical Activity Enjoyment Scale (PACES; Kendzierski, D., & DeCarlo, K. J. [1991]. Physical activity enjoyment scale: Two validation studies. Journal of Sport and Exercise Psychology, 13, 50–64. doi:10.1123/jsep.13.1.50), and the Godin Leisure Time Exercise Questionnaire (GLETQ; Godin, G., & Shephard, R. J. [1985]. A simple method to assess exercise behaviour in the community. Canadian Journal of Applied Sport Sciences, 10, 141–146. doi:10.1037/t31334-000). Somewhat contrary to the predictions of the 2 × 2 model, we obtained significant interactions between SOP and SPP for boredom in exercise only. More specifically, the highest levels of boredom were associated with high levels of SOP and low levels of SPP ("pure personal standards perfectionism" in the parlance of the 2 × 2 model). In addition, SOP was a significant negative predictor of weekly, mild, moderate, and strenuous exercise minutes and a significant positive predictor of enjoyment. SPP positively predicted mild and moderate exercise. These findings do not offer full support for the use of the 2 × 2 model but we suggest that the model may be better suited for more achievement related environments.